PERBANDINGAN IMPLEMENTASI DIGITALISASI PELAYANAN PUBLIK ANTARA KOTA PALEMBANG DAN KOTA SURABAYA - Andini Sakilla Candra; Annisa Euis Andhini; M Imam Maulidandy; Dr. Katriza Imania, M.Si,; Rizka Azzahri, S.Sos.,M.Si; Riza Adelia Suryani, S.Sos.,M.Si; Nabilla Dwi Maharani (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2025)
The development of information and communication technology (ICT) has become a key catalyst in transforming public services toward more efficient, transparent, and participatory systems. The Indonesian government, through the Electronic-Based Government System (SPBE) policy, encourages the acceleration of digitalization across all regions; however, its implementation still shows disparities between regions. This study aims to compare the implementation of public service digitalization between Palembang City and Surabaya City using the Systematic Literature Review (SLR) method. The analysis was conducted on 50 scientific journals published between 2015 and 2025, obtained from databases such as Google Scholar, Scopus, DOAJ, and the Garuda Portal, using the keywords: public service digitalization, e-government, smart city, Palembang, and Surabaya. The results indicate that Surabaya has reached the digital integration stage, supported by strong local policies, adequate technological infrastructure, and high public participation through various digital service innovations such as the Surabaya Single Window (SSW), e-Musrenbang, and the Command Center. In contrast, Palembang remains at the digital adaptation stage, facing challenges in infrastructure, human resource capacity, and digital literacy. In conclusion, the success of public service digitalization depends not only on technological aspects but also on the synergy between adaptive policies, bureaucratic readiness, and the level of public participation. This study recommends strengthening local policies and enhancing digital literacy among citizens to accelerate the effectiveness of SPBE implementation across Indonesia.